Ajaran Agama Hindu Dalam Gaguritan Segara Rupek - Ida Made Windya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Today's Balinese language and literature are still alive and growing as a means of communication among the people, especially the Balinese. There are many forms of literary work, one of which is Gaguritan. Gaguritan as a classic literary work implies religious teachings and other knowledge that really need to be studied to understand the values contained in the Gaguritan literature. One of these literary works is in Gaguritan Segara Rupek, which is a classic literary work containing a lot of moral and religious knowledge. Segara Rupek's Gaguritan teachings provide motivation to improve the quality of behavior in society. Judging from its content, the whole Gaguritan Segara Rupek contains quite a lot of religious teachings such as tattwa and ethics. This scientific work is in the form of a descriptive qualitative design. Data was collected using literature and interview methods. From the results of data analysis, it was found that the teachings contained in Gaguritan Segara Rupek included: divine teachings, karmapala, compassion and morals. Keywords: Hindu Religion; Gaguritan Segara Rupek